The Influence of Good Corporate Governance on Firm Performance (A Study in PT. Bank XYZ Indonesia Tbk.) - Andika, Zidni Fahra (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2018)
This study aims to determine the effect of good corporate governance on firm performance. This explanatory research, explains causal relationship between the variables through hypothesis testing, using quantitative approach. Using simple random sampling, 113 employees are selected as the sample. This study uses multiple linear regression analysis. The result shows that GCG influences firm performance. In addition, transparency, accountability, responsibility, independency, and fairness partially give a significant effect on firm performance. Furthermore, the Adjusted R Squared value shows that the contribution of GCG on firm performance is 77,6% KEYWORDS: Good Corporate Governance, Firm Performance.